Ações construtivas de educação em saúde para o pré-natal - Fagundes, Daniely Quintão (2015)
The maternal and child health has currently been studied in order to improve the health conditions of women and babies. However, in order to reach this goal, it is necessary that the woman, the family, and health professionals are involved in a process of dialogue and mutual understanding. Thus, it is fundamental to perform humanized researches directed to the education of actors of this complex network involving the production of health. The aims of this study were to build a health education proposal for prenatal with pregnant women and health professionals from a Basic Health Unit, and discuss the education democratization process in health in the prenatal through education and awareness from the application of action research methodology inspired by the ideas of Paulo Freire and René Barbier. The data were analyzed from the participant observation, the development of a field diary, a survey of the themes and generative words, coding and decoding, and from there, the partial and final evaluation of the process with the proposition of reality transformation actions. The results of this study showed that health professionals and pregnant women contributed in different and complementary way in choosing topics for education in prenatal, furthermore were highlighted organizational and structural problems. That hinder the performance of activities, making it necessary reflections actions involving management and directors of the National Health System to promote expanded solutions to the problems encountered in practice.